Análise de ruído em terminais de transporte coletivo urbano: desenvolvimento de modelos de previsão - Rodrigues, Frederico (2006)
As the use of public transportation in medium and large cities becomes more and more popular, the number of urban bus stations connecting transport systems increases dramatically. As a result, the continuous traffic of heavy vehicles has produced disturbing noise levels inside the stations. Hence, the main goal of this research is to develop and implement statistical models for the prediction of the overall noise levels inside the bus stations. They are multiple regression models based on experimental data obtained from acoustic field measurements. In addition, some parameters are related to the noise generation and to the limits of acceptable community noise levels. It is also suggested an alternative solution to the problem by using noise control techniques at the source. The statistical models were then validated by comparing the results with those found in the literature. The main assumptions and limitations of the models are also discussed. This research was undertaken as a result of the need to improve the available analytical tools for the prediction of traffic noise inside buildings. There are significant opportunities for further development and implementation of the models derived in this study.